Entropy optimized phase transitions and improved thermoelectric performance in n-type liquid-like Ag9GaSe6 materials. (June 2018) - Jiang, B.; Qiu, P.; Chen, H.; Huang, J.; Mao, T.; Wang, Y.; Song, Q.; Ren, D.; Shi, X.; Chen, L.
Abstract: Liquid-like materials have shown extremely low thermal conductivity down to the minimum level in solids and high thermoelectric (TE) figure of merit above 2.0 in a few typical Cu-based compounds. These features make liquid-like materials among the top class in TEs. However, the ultrahigh TE performance is mainly reported in p-type materials. Advanced TE technology urgently requires both excellent p- and n-type materials. In this study, we introduce entropy engineering to greatly improve the figure of merit in Ag9 GaSe6 -based n-type liquid-like materials. Through successfully alloying Te at Se sites, material's configurational entropy is obviously increased to optimize phase transition characters and reduce lattice thermal conductivity. In addition, the 'electron–crystal' behavior is well maintained to achieve good electrical properties because alloying Te at Se sites scarcely affect the bottom of conduction band. Furthermore, the origin of very low lattice thermal conductivity in the low-temperature phase is revealed and attributed to the large directional Ag vibrations. All these features make Ag9 GaSe6 -based compounds excellent n-type liquid-like materials. A maximum figure of merit ( zT ) value around 1.6 at 850 K is realized in the high entropy Ag9 GaSe5.53 Te0.45, which is the best value in n-type liquid-like materials reported so far. Graphical abstract: Highlights: A reduced lattice thermal conductivity is achieved by increasing configurational entropy in Ag9 GaSe6 -based compounds. -The origin of intrinsically ultralow lattice thermal conductivity is attributed to the large directional Ag vibrations. A maximum zT around 1.6 is obtained at 850 K.